1998
DOI: 10.3758/bf03330608
|View full text |Cite
|
Sign up to set email alerts
|

Rats’ object-in-place encoding and the effect of fornix transection

Abstract: We studied the perception of simple computer-generated scenes by normal and fornix-transected Dark Agouti rats. In Experiment 1, the rats were rewarded for approaching trial-unique variable scenes differing from a constant scene that was the same across trials (constant-negative paradigm). The groups performed equivalently when scenes differed only in their objects or only in the occupied positions; however, when two scenes shared an object-place combination, the normal rats were more likely to see them as sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 35 publications
0
10
1
Order By: Relevance
“…The performance of the fornix group on the object-in-context task lay between the good performance of the sham and perirhinal groups and the impaired performance of the postrhinal group. There have been previous reports of impairments in object-in-context tasks in rats following damage within the hippocampal system (Mumby et al, 2002; Simpson, Gaffan, & Eacott, 1998). There is also evidence that context can modify the output of hippocampal place cells (for a review, see Jeffery, Anderson, Hayman & Chakraborty, 2004), which may suggest a mechanism for such an effect.…”
Section: Discussionmentioning
confidence: 99%
“…The performance of the fornix group on the object-in-context task lay between the good performance of the sham and perirhinal groups and the impaired performance of the postrhinal group. There have been previous reports of impairments in object-in-context tasks in rats following damage within the hippocampal system (Mumby et al, 2002; Simpson, Gaffan, & Eacott, 1998). There is also evidence that context can modify the output of hippocampal place cells (for a review, see Jeffery, Anderson, Hayman & Chakraborty, 2004), which may suggest a mechanism for such an effect.…”
Section: Discussionmentioning
confidence: 99%
“…The objects in each pool were always from a different shape class than their corresponding constant object (e.g., the leftmost object in the constant scene of is a polygon, so its pool of objects comprised crosses, ellipses, letters, rectangles, or disks, but no polygons). Simpson and Gaffan (1999) showed that rats were especially sensitive to form differences between objects when they were from different shape classes, hence our decision to use different classes for Type O+P and O. Another reason is that the three objects within the constant scene were from different shape classes, therefore using different classes for Type O scenes would produce as much shape change as when constant objects were switched around for Type OP.…”
Section: Methodsmentioning
confidence: 99%
“…For variable types in which position differed, namely O+P and P, the position of an object in any variable scene differed by one step on the 4 × 4 grid in any direction (vertical, horizontal, diagonal) randomly from that of the same object in the constant scene, subject to the constraint that it remained within the 4 × 4 grid and did not overlap any other object. We chose this amount of position separation, on the basis of the findings of Simpson, Gaffan, and Eacott (1998), so as to be similar in discriminability to the object differences in Types O+P and O. Because there were few possible positions for any object in a variable scene, particular positions were reused across variable scenes in the same session, but specific combinations of three positions rarely recurred across scenes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gaffan & Eacott, 1997;E. A. Gaffan, Eacott, & Simpson, 2000;Simpson & Gaffan, 1999;Simpson, Gaffan, & Eacott, 1998). We use them to investigate the nature and neural basis of rats' ability to encode aspects of scenes-the shapes or figures that the scenes contain, their positions within the scene, and the combinations or configurations of these elements.…”
mentioning
confidence: 99%